The ipsilateral silent period: an early diagnostic marker of callosal disconnection in ALS. (September 2021) - Hübers, Annemarie; Kassubek, Jan; Müller, Hans-Peter; Broc, Nicolas; Dreyhaupt, Jens; Ludolph, Albert C.
Introduction: Imaging studies showed affection of the corpus callosum (CC) in amyotrophic lateral sclerosis (ALS). Here, we sought to determine whether these structural alterations reflect on the functional level, using transcranial magnetic stimulation (TMS). Methods: In 31 ALS patients and 12 controls, we studied mirror movements (MM) and transcallosal inhibition (TI) using TMS. Structural integrity of transcallosal fibres was assessed using diffusion tensor imaging. Results: TI was pathologic in 25 patients (81%), 22 (71%) showed MM. Loss of TI was observed in very early stages (disease duration <4 months). No correlation was found between TI/MM and fractional anisotropy of transcallosal fibres. Discussion: These results substantiate the body of evidence towards a functional involvement of the CC in early ALS beyond microstructural alterations. Significance: TI may become a useful early diagnostic marker in ALS, even before descending tracts are affected. Diagnostic delay in ALS is high, often preventing patients from gaining access to therapeutic trials, and sensitive diagnostic tools are urgently needed. Our findings also provide insights into the pathophysiology of ALS, potentially supporting the so-called 'top-down' hypothesis, that is, corticoefferent (intracortical/corticospinal) propagation. Callosal affection in early stages might represent the 'missing link' to explain corticocortical disease-spreading.